Pengembangan Sistem Pendeteksi Kadar Asap Rokok Dalam Ruangan Berbasis MQ-135 - Septiya Hanum Pratiwi; Muchtar Ali Setyo Yudono (LPPM POLBITRADA, 2025)
Cigarette smoke is one of the main sources of indoor air pollution that contains harmful chemical compounds such as carbon monoxide, ammonia, and other particles that can disrupt the human respiratory system. To monitor and detect unhealthy air conditions due to cigarette smoke, this study aims to develop an air quality detection system based on the Wemos D1 microcontroller with MQ-135 and DHT11 sensors. The system is designed to identify bad air parameters based on MQ-135 values above 400 ppm, temperatures above 30°C, and humidity below 40%. The sensor reading results are displayed in real-time on a 128x64 OLED screen and stored into the SD Card memory card. In addition, the buzzer will activate as a warning alarm when the air conditions are declared unhealthy. System development involves the integration of hardware and software, with a focus on accuracy, efficiency, and ease of use. It is hoped that this system can help users in effectively monitoring air quality and take preventive measures to reduce the risk of health problems due to indoor cigarette smoke exposure.